2009
DOI: 10.1016/j.jecp.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory facilitate predictive tracking in 4-month-olds

Abstract: We investigated 4-month-olds' oculomotor anticipations when viewing occlusion stimuli consisting of a small target that moved back and forth repetitively while the center of its trajectory was occluded by a rectangular screen. We examined performance under five conditions. In the baseline condition, infants produced few predictive relative to reactive eye movements. In the full training condition, anticipations were increased in frequency following prior exposure to a target moving along a fully visible trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…Other work (Vishton, Ware, & Badger, 2005) has shown similar changes in sensitivity to certain Gestalt cues when the action task changes (e.g., from looking to object-directed reaching). In this regard, our findings can be linked with a range of empirical results demonstrating infant learning and transfer (Johnson & Shuwairi, 2009; Lany & Gomez, 2008; Needham, Dueker, & Lockhead, 2005; Wilcox & Chapa, 2004), as well as with dynamic systems and connectionist theory, which can readily accommodate situations in which changes in a single variable in a particular study can cause large changes in infants’ performance (e.g., Spencer, Thomas, & McClelland, in press). …”
Section: Discussionsupporting
confidence: 57%
“…Other work (Vishton, Ware, & Badger, 2005) has shown similar changes in sensitivity to certain Gestalt cues when the action task changes (e.g., from looking to object-directed reaching). In this regard, our findings can be linked with a range of empirical results demonstrating infant learning and transfer (Johnson & Shuwairi, 2009; Lany & Gomez, 2008; Needham, Dueker, & Lockhead, 2005; Wilcox & Chapa, 2004), as well as with dynamic systems and connectionist theory, which can readily accommodate situations in which changes in a single variable in a particular study can cause large changes in infants’ performance (e.g., Spencer, Thomas, & McClelland, in press). …”
Section: Discussionsupporting
confidence: 57%
“…An important question for future research is whether, and if so, how experience constrains the development of this interaction in occlusion situations. Johnson and colleagues (Johnson, Amso, & Slemmer, 2003;Johnson & Shuwairi, 2009), for instance, recently showed that infants as young as 4 months are able to learn to perform anticipatory eye movements from experiencing a few related visual events only. Can experience also accelerate development of anticipatory reaching?…”
Section: Discussionmentioning
confidence: 99%
“…Infants can learn across trials to make appropriate predictive eye movements when observing inanimate objects move [13][14][15], and evidence of this learning has been found before they are able to perform objectdirected reaches [14,16]. Alternatively, and in line with assumptions about mechanisms underlying predictive eye movements towards object-directed actions [1,2,17], the mirror system may play a role.…”
Section: Discussionmentioning
confidence: 99%